MIM (Maghrib Isya Mengaji): An Innovation in Mosque-Based Al-Qur'an Learning for Parents. - Widadi, Ahmad Setyo; Iksan, Iksan (Instructional Development Journal, 2025)
This study aims to explore the effectiveness of the Maghrib Isya Mengaji (MIM) program as an innovation in mosque-based Quranic learning at At-Taqwa Mosque, Simorejo, Surabaya. The program is designed to improve the quality of Quranic recitation among the community, particularly the elderly, using the talaqqi method, which involves direct guidance from professional instructors. This research employs a qualitative approach, utilizing observation, semi-structured interviews, and documentation. The informants include mosque management (takmir) and congregants actively participating in the program. The findings reveal that the MIM program has successfully improved participants' Quranic recitation skills in terms of fluency and the application of tajweed rules. Additionally, the program has had a positive spiritual impact, such as increasing participants’ connection to the Quran, fostering motivation for more frequent Quranic recitation, and strengthening social relationships between congregants and the mosque. Supporting factors for the program's success include full support from the mosque management, adequate facilities, and the enthusiasm of the congregants. However, challenges remain, such as participants' reluctance to learn due to embarrassment, limited time, and the occasional absence of competent instructors. In conclusion, the MIM program is effective in facilitating inclusive and sustainable mosque-based Quranic learning, providing a solution for busy individuals to continue improving their Quranic literacy. The results of this study are expected to serve as a reference for other mosques to implement similar programs, reinforcing the mosque's role as a center for education and Islamic civilization. Keywords : Innovation, MIM, Mosque, Learning